FORMULASI DAN EVALUASI GEL EKSTRAK DAUN TAHI BELALANG PADA LUKA BAKAR KELINCI - Lende, Yulianus Erman; Hidayat, Rahmat; Listyani, Tiara Ajeng (Jurnal Buana Farma, 2025)
Burn wounds are a common health issue that requires effective management. This study explores the potential of tahi belalang leaf extract (Chromolaena odorata L.) as a healing agent for burn wounds, with bioactive compounds such as flavonoids, saponins, tannins, and alkaloids that possess anti-inflammatory, antioxidant, and anti-allergic properties. The main objective is to formulate and evaluate the gel preparation of tahi belalang leaf extract as an alternative topical treatment. The research method involves plant determination, preparation, standardization of simplicia, extraction, and phytochemical screening to identify active compounds. Subsequently, gel formulations were created with varying concentrations of extract (5%, 10%, 15%) and the physical quality of the preparations was evaluated (organoleptic, homogeneity, pH, viscosity, spreadability, adhesion, irritation, and hedonic). The effectiveness of burn wound healing was tested in vivo on male rabbits, comparing the gel formula with a negative control (gel base) and a positive control (Bioplacenton®), with daily wound diameter measurements and statistical analysis using SPSS. The results showed that the gel containing 15% tahi belalang leaf extract (F3) was the most effective formulation in accelerating the healing of second-degree burn wounds in male rabbits. The presence of flavonoids, alkaloids, tannins, and saponins contributed anti-inflammatory, antioxidant, and antibacterial effects that supported tissue regeneration. Based on the ANOVA significance value of 0.028, there was a statistically significant difference among the treatment groups of the formulations.